MAJAS SINDIRAN DALAM HUMOR SBY-JK (SUSAH BENSIN YA JALAN KAKI) KARYA WAHYU UNTARA - Yury Azura; Hasnah Faizah; Auzar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The title of research is ”Majas Sindiran dalam Humor SBY-JK (Susah Bensin Ya Jalan Kaki) created by Wahyu Untara.” The purpose of the research to describe form and the meaning of irony (majas sindiran) in the humor SBY-JK (Susah Bensin Ya Jalan Kaki) created by Wahyu Untara. The type of the research that used are qualitative research with used descriptive method. The data that used in the research is the shape of irony (majas sindiran) in the book of humor SBY-JK (Susah Bensin Ya Jalan Kaki) created by Wahyu Untara. The result of the research that writer found of in this research there are five form of irony (majas sindiran) that found of iroby (majas sindiran) ij the book of humor SBY-JK (Susah Bensin Ya Jalan Kaki) created by Wahyu Untara are majas sarkasme, irony, sinisme, innuendo, and antiphrasis. Among the form of majas, dominant the form that found is majas sindiran (in form irony). At the study, writer uses analysis method based on the contextual meaning to study the meaning of each the majas sindiran.Key words: majas sindiran, humor SBY-JK (Susah Bensin Ya Jalan Kaki), form of majas sindiran, the meaning of majas sindiran.